Development of Neuroscience-Based Biology Learning Media to Increase Learning Motivation and Cognitive Learning Outcomes of Tenggarong High School Students - Yuli Rian Andriyani Sinaga; Herliani; Didimus Tanah Boleng; Elsje Theodora Maasawet; Akhmad; Vandalita M. M Rambitan (Jurnal Penelitian Pendidikan IPA, 2024)
Neuroscience-based learning is a field of neuroscience study that focuses on studying educational concepts from the perspective of the brain's working system. It turns out that teachers and parents still rarely pay attention to this field of study, which has led to the emergence of a learning atmosphere that is passive and not optimal in stimulating nerve cells in the human brain. The results of initial observations carried out on 22-28 April 2021 on high school teachers and students in Tenggarong (SMA Negeri 1 Tenggarong, SMA Negeri 2 Tenggarong, SMA Negeri 3 Tenggarong) showed that there were still many (85%) It was found that teachers still relied on verbal language, image/animation media, PowerPoint and only a few (15%) were varied in their use of biology learning media, although based on interviews they said they understood audio, visual and audiovisual media well enough. Likewise with learning with neuroscience-based media, from the interview results, generally (85%) were not familiar with biology learning with neuroscience-based media and only a few (15%) were familiar with and had implemented it in biology learning. The same thing applies to students' cognitive learning outcomes from interviews that I found that students' abilities were generally moderate and low. This is because students think that biology is a rote subject and are less motivated when learning. This research method is Research and Development (R&D) Sivasailam Thiagarajan. The main objective of this development research method is to produce products and determine the feasibility of products developed in the form of neuroscience-based learning videos which are limited to the circulatory system. The research subjects included four validator experts, namely media experts, materials experts, language experts and learning tools experts. Class XI students as the research sample consisted of two classes, namely the control class and the experimental class. The results of the research show that the validity of learning media is in the valid category (79.95%), the practicality of learning media is in the very good category (83.37%), and also the effectiveness of neuroscience-based learning media in providing a high increase in learning motivation (Gain score = 0 .73) and t test analysis (t count < 0.05) via the SPSS application.